PERAN MANAJEMEN KREATIVITAS DAN INOVASI TERHADAP KEUNGGULAN KOMPETITIF ORGANISASI (STUDI LITERATURE BERBASIS PENGETAHUAN) - Ananda Kristopel Siregar1; Iqbal Wahyu Ardian, M. Yasir Mekotonda, Tri Yulaeli (Jurnal Ekonomi dan Bisnis, 2024)
Research analyzing creativity and innovation management based on human resource knowledge is a scientific literature article in the scope of Creative and Innovation Business. The aim of this literature research is to build hypotheses regarding the influence between variables which can later be used for further research within the scope of Creative Business and Innovation. The approach used in this research is descriptive qualitative. The data collection technique is using literature study. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as Scopus Elsevier Journal, Emerald, WoS, Sinta Journal, DOAJ, EBSCO, GARUDA, Google Scholar and digital reference books. The results of this literature article include: 1) Creativity Management plays a role in Organizational Competitive Advantage; and 2) Innovation plays a role in the Organization's Competitive Advantage.